UPAYA BADAN NASIONAL PENGELOLA PERBATASAN DALAM MENANGANI MASALAH KEAMANAN DI INDONESIA-PAPUA NUGINI - Frinsiska Manurung; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Since the independece of Papua New Guinea in 1975, the border is more or less 780 km between Papua New Guinea and Indonesia (Papua Province) has become suspicion embrio between the both states involved the border issue. Indonesian has implemented the efforts of diplomacy and intimidation to prevent Papua New Guinea to become the protection place of border crossing for the separatist group, such Independent Papua Organization. Besides that, there are still many lawsuits that are caused by the weak management and law inforcement in the area of the both states.The perspective is Centripental Democratic Governance because the decentralization doesn’t give the advantage forever. The teory in this research is decision making and written by Richard Snyder. The level analysis is nation state and written by Charles W Kegley Jr dan Eugene R Wittkopf. The data is obtained through primary data and secunder data such as, book, journal, magazine, newspaper and website.This study aims to find out how the government of Indonesia acts significant in managing the border area in making Badan Nasional Pengelola Perbatasan (BNPP). This organization coordinates the both states by using three approaches in managing the border area, namely approach of security, wealth, and environment.Key words: The Border, BNPP, Operasi Papua Merdeka, Human Security